2012
DOI: 10.1371/journal.pone.0046808
|View full text |Cite
|
Sign up to set email alerts
|

Mir-206 Regulates Pulmonary Artery Smooth Muscle Cell Proliferation and Differentiation

Abstract: Pulmonary Arterial Hypertension (PAH) is a progressive devastating disease characterized by excessive proliferation of the Pulmonary Arterial Smooth Muscle Cells (PASMCs). Studies suggest that PAH and cancers share an apoptosis-resistant state featuring excessive cell proliferation. MicroRNA-206 (miR-206) is known to regulate proliferation and is implicated in various types of cancers. However, the role of miR-206 in PAH has not been studied. In this study, it is hypothesized that miR-206 could play a role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…Reduction of miR-206 in human PASMCs causes increased proliferation and reduced apoptosis, which are key histopathological features of PAH. These results suggest that miR-206 is a potential regulator of proliferation, apoptosis, and differentiation of PASMCs (135). Although the role of miR-206 in SMC proliferation has not been examined in early developing lungs, reduced expression of miR-206 by Shh might not only be responsible for the increased innervation of SMCs, but also for the promotion of SMC proliferation.…”
Section: Mir-133 In Smc Differentiationmentioning
confidence: 95%
“…Reduction of miR-206 in human PASMCs causes increased proliferation and reduced apoptosis, which are key histopathological features of PAH. These results suggest that miR-206 is a potential regulator of proliferation, apoptosis, and differentiation of PASMCs (135). Although the role of miR-206 in SMC proliferation has not been examined in early developing lungs, reduced expression of miR-206 by Shh might not only be responsible for the increased innervation of SMCs, but also for the promotion of SMC proliferation.…”
Section: Mir-133 In Smc Differentiationmentioning
confidence: 95%
“…Overexpression of miR-124 not only inhibited human PASMC proliferation, but also maintained its differentiated phenotype by repressing the NFAT pathway (55). It was reported that miR-206 regulates PASMC proliferation and differentiation (56) and that miR-210 has antiapoptotic effects in PASMCs during hypoxia (57). Courboulin et al reported that miR-204 plays a role in human PAH and PA remodeling (58).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Notch signaling has also been closely associated with apoptosis and cell survival, especially in cancer cells (9, 28 -36) and smooth muscle cells (11,14,25,37,38). Notch3 specifically has been shown to promote cell survival in several different cell types (9,11,25,(33)(34)(35)37) and is a poor prognostic biomarker in several cancers (29,30,39).…”
mentioning
confidence: 99%